Fitoremediasi Tumbuhan Belimbing Bajo (Sarcotheca celebica Veldk.) dalam Menyerap Logam Berat Nikel - Risman, Risman; Ndibale, Wa; Wibowo, Dwiprayogo (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2025)
Phytoremediation offers an environmentally friendly and cost-effective approach to mitigate heavy metal pollution by utilizing plants capable of absorbing and accumulating contaminants. This study explores the phytoremediation potential of Bajo starfruit (Sarcotheca celebica Veldk.) to absorb Ni from contaminated post-mining soil. This research aims to assess the absorption capacity of Sarcotheca celebica Veldk. for Ni and evaluate its feasibility as a phytoremediator. The Ni concentration in the soil was measured before and after planting to determine the reduction level attributable to the plant. Initial measurements showed a total Ni concentration of 0.32% in the soil. After a designated growing period, during which the plant entered the vegetative growth phase, the Ni concentration decreased to 0.29%, indicating an absorption capacity of 0.03%. The potential application of Sarcotheca celebica Veldk. as a native phytoremediation agent in sustainable post-mining land restoration programs. Its adaptation to local environmental conditions further supports its use in ecological rehabilitation strategies aimed at restoring the functionality of degraded ecosystems.